Gap Analysis of existing managerial skill set and the skills imparted by the management institutes for the IT Industry - Aman Chadha; Akriti Gupta; Vijayshri Tewari (International Ecsis Association, 2022)
Nowadays, it becomes more important to produce rightly skilled individuals with the skills to survive and flourish in the industry. This paper focuses on the skill set that the management institutes are developing and how well that skill set is catering to the current era's IT industry. Such a sample population covers all the IT firms of India, registered as authorized companies and management institutes of the country that follow the overall accepted curriculum for management studies. A sample of 54 respondents was taken. The survey was done, questionnaires were floated to gather data, and further IBM SPSS was used for statistical analysis and to interpret the results. This research reveals a huge gap between the skills required and the skill set provided. It also brings out the key factors to address to fill the gap. Not only the factors but also the best possible methods to overcome such gaps have been brought to light in this paper. It gives an insight into the industry's dynamics and how important it is to cope with them for survival.